Performance Enhancement of Shell and Tube Heat Exchanger on Parallel Flow with Single Segmental Baffle - Permanasari, Avita Ayu; Puspitasari, Poppy; Sukarni, Sukarni; Wulandari, Retno (Journal of Mechanical Engineering Science and Technology (JMEST), 2020)
The shell and tube heat exchanger was a tool to exchange the heat energy between fluids with different temperatures that occurred through direct or indirect contact. The energy exchange in fluids could be occurred with the same phase (liquid to liquid or gas to gas) or two fluids with different phase. To date, the process of heat transfer in the industrial field was crucial in machine work. Therefore, there were studies directed to optimize and develop the function and thermal performance of a heat exchanger by adding Baffles to the side of the shell. Vortex flow that occurs with the addition of baffles will make the area of fluid contact in the shell with the tube wall larger, so the heat transfer between the two fluids will increase. This study aimed to obtain the efficiency of the heat exchanger and its effectiveness when put on parallel flow. The heat exchanger had the dimensions of 54.6 x 10-3 m in outer diameter and 22.4 x 10-3 m in inner diameter with a tube thickness of 3 mm. The variations on water flow from both fluids were 0.5, 1, 1.5, 2 l/min for hot water and 1, 2, 3, 4 l/min for cold water to obtain the effectiveness of heat exchanger on parallel flow. This research heated the hot fluid in electric heating and used water as the cold fluid. The results showed that heat exchanger with single segmental baffle was more efficient in reducing heat in hot water than heat exchanger without bafe. The flow of fluid affected the average temperature difference; the higher the flow of fluid created a more significant temperature difference. The use of single segmental baffle affected the average temperature difference that was higher than without the baffle. The use of single segmental baffle also influenced the heat transfer greater than without baffle because of the longer distance travelled by the fluid on single segmental baffle with the same flow. Thus, the heat transfer process that occurred was more significant by using a single segmental baffle.